Pengaruh Media EarthScapeLab terhadap Hasil Belajar Gerhana Bulan dan Matahari Siswa Kelas VI SDN Sendang Laok Bangkalan - Adinda Sekar Arum Cahyani; Bintang Agustin Mulyasari; Ika Dian Rahmawati (CV.ITTC INDONESIA, 2026)
This study aims to determine the effect of EarthScapeLab media on the learning outcomes of Grade VI students at SDN Sendang Laok Bangkalan on the topic of lunar and solar eclipses. A quantitative approach with a one-group pre-test post-test design was employed. The research subjects were 12 Grade VI students selected through total sampling. The instrument used was a multiple-choice test covering lunar and solar eclipse material. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Paired Sample T-Test, and N-Gain Score. Results showed the mean score increased from 45.8 on the pre-test to 80 on the post-test, exceeding the minimum mastery criteria. The Paired Sample T-Test yielded a significance value of 0.000 (< 0.05), indicating a statistically significant difference in learning outcomes before and after the intervention. N-Gain analysis showed an average score of 0.61, categorized as moderate. Therefore, EarthScapeLab media is proven effective in improving student learning outcomes on the topic of lunar and solar eclipses in Grade VI at SDN Sendang Laok Bangkalan.